Online Course - SALT - Sustainable Aquaculture for Low Trophic Species - Kochanska, Adrianna; Aschan, Michaela; Strand, Åsa; James, Philip; Gombau, Ronan; Gunnarsdóttir, Katrín Hulda (2023)
The course is made up of 11 modules including 9 topics in 103 educational videos and over 400 assessment questions. The modules cover various topics, including the biology of the four species groups (molluscs, macroalgae, echinoderms, freshwater fish), the design and operation of the cultivation practices, and their environmental impact. Furthermore, you will explore the economic and social aspects of aquaculture and the policies and regulations that govern the industry. The interdisciplinary approach will deepen your understanding of the subject matter and provide you with the knowledge and skills essential to contribute to a sustainable industry. A YouTube video (link below) gives a short introduction about the course.